1993
DOI: 10.1136/adc.68.3.384
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, depression, and social adjustment in chronic fatigue syndrome.

Abstract: The aims of this study were to determine the characteristics and perceived levels of fatigue and the prevalence of depression in children with chronic fatigue syndrome and to assess

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
4

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 21 publications
3
45
4
Order By: Relevance
“…In addition, the present study found no specific thought and attention problems, normal achievement motivation, and elevated positive and reduced negative fear of failure, reflecting an adaptive way of coping with stressful circumstances. Several of these findings contradict previous studies that do report social isolation, 7,10,13,15 attention and concentration problems, 2,10,20,25 and high achievement motivation and perfectionism. 1,5,8 Although the patients in this study did report concentration problems in the semi-structured interview, when asked about their symptoms, they did not report significantly heightened thought and attention problems on the emotional and behavioral problems scale.…”
Section: Psychosocial Functioning and Distresscontrasting
confidence: 56%
See 1 more Smart Citation
“…In addition, the present study found no specific thought and attention problems, normal achievement motivation, and elevated positive and reduced negative fear of failure, reflecting an adaptive way of coping with stressful circumstances. Several of these findings contradict previous studies that do report social isolation, 7,10,13,15 attention and concentration problems, 2,10,20,25 and high achievement motivation and perfectionism. 1,5,8 Although the patients in this study did report concentration problems in the semi-structured interview, when asked about their symptoms, they did not report significantly heightened thought and attention problems on the emotional and behavioral problems scale.…”
Section: Psychosocial Functioning and Distresscontrasting
confidence: 56%
“…Reported results include considerable restrictions to physical activities, social activities, and school attendance. 1,15,16 Besides, high achievement motivation and perfectionism (adolescents, 1,5,13,14 adults 8,17 ) are described. High internalizing symptoms (eg, anxiety, withdrawn, and overcontrolled behavior) are found, as well as difficulties with regard to social relationships, but no consistent differences regarding family functioning.…”
mentioning
confidence: 99%
“…Whether such treatments can be instituted in a primary care setting, as is suggested for the majority of patients with chronic fatigue syn drome by the Royal Colleges' report (Royal College of Physicians, Royal College of Psychia trists and Royal College of General Practit ioners, 1996), is open to debate. These patients present GPs with considerable difficul ties (Scott et al, 1995), and they and their families may be reluctant to attend for a psychiatric appointment even though psychi atric symptoms, such as depression, are often present (Walford et al, 1993). Such issues may be reflected in the lack of agreement amongst GPs in our survey as to whether a psychiatrist should become involved.…”
Section: Commentmentioning
confidence: 41%
“…It has been suggested that the depressed mood may be reactive to the chronic physical symptoms in CFS. However, this has not been supported by a study comparing depressive symptomatology in children with CFS to those suffering the chronic physical illness of cystic fibrosis (Walford et al 1993). Even if reactive, untreated depressive symptoms can become chronic and disabling (Lynch, 1994).…”
Section: Commentmentioning
confidence: 79%